(untitled) (Research, Society and Development, 2021)
This study aims to identify the drugs used most frequently among patients on hemodialysis and to identify possible drug interactions between such drugs. This is a cross-sectional study carried out in the hemodialysis sector of a hospital. The crossing between drugs was studied in the Interage - Drug Interactions program, in order to identify potential drug interactions and classify them according to severity. The total number of patients studied was 45 individuals, of which 47% were men. The drugs most frequently used by patients were Omeprazole (22.35%), followed by Erythropoietin (11.40%). There were 113 drug interactions, 38 of which were mild MI (33.63%), 60 moderate MI (53.10%) and 15 severe MI (13.27%). The prevalence of drug interactions in patients on hemodialysis was considered high. Individuals on hemodialysis therapy lack the use of several medications, so it is extremely important to carefully select therapeutic solutions for the effective, rational and safe use of these medications.